Phosphoproteomic and proteomic profiling in post-infarction chronic heart failure - Wang, Jiayue; Zhu, Xiuhua; Wang, Shenrui; Zhang, Yingjie; Hua, Wenjie; Liu, Zhenyu; Zheng, Yu; Lu, Xiao (Frontiers in Pharmacology, 2023)
Background: Post-infarction chronic heart failure is the most common type of heart failure. Patients with chronic heart failure show elevated morbidity and mortality with limited evidence-based therapies. Phosphoproteomic and proteomic analysis can provide insights regarding molecular mechanisms underlying post-infarction chronic heart failure and explore new therapeutic approaches. Methods and Results: Global quantitative phosphoproteomic and proteomic analysis of left ventricular tissues from post-infarction chronic heart failure rats were performed. A total of 33 differentially expressed phosphorylated proteins (DPPs) and 129 differentially expressed proteins were identified. Bioinformatic analysis indicated that DPPs were enriched mostly in nucleocytoplasmic transport and mRNA surveillance pathway. Bclaf1 Ser658 was identified after construction of Protein-Protein Interaction Network and intersection with Thanatos Apoptosis Database. Predicted Upstream Kinases of DPPs based on kinase–substrate enrichment analysis (KSEA) app showed 13 kinases enhanced in heart failure. Proteomic analysis showed marked changes in protein expression related to cardiac contractility and metabolism. Conclusions: The present study marked phosphoproteomics and proteomics changes in post-infarction chronic heart failure. Bclaf1 Ser658 might play a critical role in apoptosis in heart failure. PRKAA1, PRKACA, and PAK1 might serve as potential therapeutic targets for post-infarction chronic heart failure.